Synthetic biology approaches to enhance cancer immune responses - Liu, Shuzhen; Zhong, Zhihao; Tu, Qihang; Jin, Meiling (Frontiers in Immunology, 2025)
Synthetic biology is being widely applied in tumor therapy, ranging from attenuating microbial toxicity to constructing synthetic gene circuits and developing CAR-T cells, all of which are reshaping the landscape of cancer immunotherapy. In this review, we summarize recent advances in microbial-based therapeutics that leverage bacteria’s natural tropism for hypoxic tumor regions to deliver immunomodulatory payloads with high spatial precision. Parallel progress in CAR-T cell engineering has led to the development of armored and logic-gated constructs designed to overcome challenges such as antigen heterogeneity, the immunosuppressive tumor microenvironment, and T cell exhaustion. Synthetic biology further integrates these platforms via programmable genetic circuits capable of performing Boolean logic operations, ensuring therapeutic activation only in the presence of tumor-specific biomarkers. While this convergence offers the unprecedented precision, safety, and potency in reprogramming anti-tumor immunity, the clinical translation of these complex systems faces significant hurdles. Despite challenges in clinical translation-including safety concerns, immune clearance, and manufacturing complexity-the field is advancing toward multifunctional “smart” therapies, synergistic microbial-cell combinations, and personalized treatment strategies. Together, these innovations are defining a new generation of precision-engineered immunotherapies with the potential to transform the treatment of refractory malignancies.